Sculpting in time : reflections on the cinema - Tarkovsky, Andrey (Austin : University of Texas Press, 1987)
he beginning -- Art : a yearning for the ideal -- Imprinted time -- Cinema's destined role -- The film image -- Time, rhythm and editing -- Scenario and shooting script -- The film's graphic realisation -- The film actor -- Music and notes -- The author in search of an audience -- The artist's responsibility -- After Nostalgia -- The sacrifice.
Originally published in German as Die Versiegelte Zeit by Ullstein Verlag in 1986. Translation of: Zapechatlennoe vremi︠a︡.
boek
Keywords: Tarkovski, Andrej